2012
DOI: 10.1117/12.973689
|View full text |Cite
|
Sign up to set email alerts
|

Change detection in time series of high resolution SAR satellite images

Abstract: In the last few years, change detection based on remote sensing data has become a highly frequented field of research with multiple applications for practical use. To detect changes between temporarily different satellite images is of interest for example in terms of urban monitoring and disaster management. The approach presented in this paper allows the fully automatic detection of small-scaled changes (e.g. vehicles or construction sites) in time series of SAR amplitude image data. To create a robust method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It is also shown that the combination of the two attributes leads to a more precise result. The detected change segments given in Figure 3 (upper half, right column) represent changes of comparable category (Boldt et al, 2012).…”
Section: Area and Std Attributementioning
confidence: 99%
See 4 more Smart Citations
“…It is also shown that the combination of the two attributes leads to a more precise result. The detected change segments given in Figure 3 (upper half, right column) represent changes of comparable category (Boldt et al, 2012).…”
Section: Area and Std Attributementioning
confidence: 99%
“…The change detection method described in (Boldt et al, 2012) requires an amplitude image pair as data input. From this image pair, a maximum ratio image is calculated.…”
Section: Detecting Similar Changesmentioning
confidence: 99%
See 3 more Smart Citations